Optimizing immunization schedules in endemic cholera regions: cost-effectiveness assessment of vaccination strategies for cholera control in Bangladesh. Issue 43 (15th October 2021) - Zeng, Wu; Cui, Yujie; Jarawan, Eva; Avila, Carlos; Li, Guohong; Turbat, Vincent; Bouey, Jennifer; Farag, Marwa; Mutasa, Ronald; Ahn, Haksoon; Sun, Daxin; Shen, Jie
Abstract: This study is to examine the cost-effectiveness of deployment strategies of oral cholera vaccines (OCVs) in controlling cholera in Bangladesh. We developed a dynamic compartment model to simulate costs and health outcomes for 12 years for four OCVs deployment scenarios: (1) vaccination of children aged one and above with two doses of OCVs, (2) vaccination of population aged 5 and above with a single dose of OCVs, (3) vaccination of children aged 1–4 with two doses of OCVs; and (4) combined strategy of (2) and (3). We obtained all parameters from the literature and performed a cost-effectiveness analysis from both health systems and societal perspectives, in comparison with the base scenario of no vaccination. The incremental cost-effectiveness ratios (ICERs) for the four strategies from the societal perspective were $2, 236, $2, 250, $1, 109, and $2, 112 per DALY averted, respectively, with herd immunity being considered. Without herd immunity, the ICERs increased substantially for all four scenarios except for the scenario that vaccinates children aged 1–4 only. The major determinants of ICERs were the case fatality rate and the incidence of cholera, as well as the efficacy of OCVs. The projection period and frequency of administering OCVs would also affect the cost-effectiveness of OCVs. With the cut-off of 1.5 times gross domestic product per capita, the four OCVs deployment strategies are cost-effective. The combined strategy is more efficient than the strategy of vaccinating the population aged one and above with two doses of OCVs and could be considered in the resource-limited settings.